Hadjigeorgiou, Eleni - (:unkn) unknown (My University, 2026)
Dr Eleni Hadjigeorgiou is an Assistant Professor, Midwifery Care, Director of the MSc programme in Midwifery at the Department of Nursing, Faculty of Health science, Cyprus University of Technology. She was midwifery educator in Nursing and Midwifery School from 1999 until 2008. She is a registered Midwife and served as a Board member of the Cyprus Nurses and Midwives Association and Nursing and Midwifery Council. She was a representative of Midwifery in local, European and International level. She has an extensive and robust teaching experience in midwifery and in running nursing educational programmes in master’s degree level and at undergraduate level. She coordinates educational programmes and research projects in Midwifery. Education: Dr Hadjigeorgiou has received a Diploma in Nursing and in Midwifery from the Cyprus Nursing and Midwifery School; her BSc (Hons) in Nursing from the Anglia University, United Kingdom and a Master’s degree in Midwifery Education from Middlesex University United Kingdom. Dr Hadjigeorgiou has received her PhD from the Cyprus University of Technology in cooperation with Middlesex University, United Kingdom, and SKOVDE University Sweden. Research Activities: Dr. Hadjigeorgiou has been involved in many innovative research project. The " Best Start in life" BrEaST, which was financed by the ESA Grants NGO (2014-2015). Second was a European Project Y-SAV Youth- Sexual Aggression and Victimization. Mrs. Hadjigeorgiou participates in a COST action IS 1405: Building Intrapartum Health Through Research-an interdisciplinary approach to whole system understanding and contextualizing labour and physiological birth (BIRTH) and specifically was Vice – Group Leader of working group WG5-Neuropsychosocial perspectives. She coordinated a quantitative research with Topic: "Mentally Healthy mothers. Mentally healthy children. Solid foundation of new generation.” She participated in an innovative project : Building health literacy around pregnancy, birth and early life of the infant by developing a unified, research-informed and socially-inclusive prenatal and postnatal web-based education programme for parents-to-be and new parents Project Acronym: Baby Buddy – Forward, Erasmus Charter for Higher Education (ERAPLUS-ECHE) CY LIMASSO02 , 36 months: 1 Sept 2017 – 31 Aug 2020, Overall budget: ~ 350.000 euro. Now she participate in COST 18211 PERINATAL MENTAL HEALTH AND BIRTH-RELATED TRAUMA: MAXIMISING BEST PRACTICE AND OPTIMAL OUTCOMES (DEVoTION) 2019-2023 Coordinator of a European study: Clinicians’ experiences of interpersonal interactions in the birth environment. Coordinator of International study : “Impact of Covid-19 Pandemic in Perinatal Mental Health (Riseup PPD-Covid)”. This international study will be carried out in 12 European countries (Albania, Bulgaria, Cyprus, France, Greece, Israel, Malta, Portugal, Serbia, Spain, Turkey, United Kingdom) and Brazil (2020-2022).
Keywords: midwifery care, childbirth rights, perinatal mental health; nursing